STRATEGI KOMUNIKASI BNN PROVINSI RIAU DALAM PENCEGAHAN PEMBERANTASAN PENYALAHGUNAAN DAN PEREDARAN GELAP NARKOBA (P4GN) - HOTMAULINA MARIA BR. HALOHO; Welly Wirman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The problem of abuse and illicit drug in many countries has become a crucial issue, including Indonesia. In Indonesia, Riau particular is an area of central western region of Indonesia that has many entrances from the outside, the year 2012 recorded the BNN of Riau drug users reached 2% and if not minimized projected in 2015 will reach 2.12%. As concrete steps to stem the abuse and illicit drug the government launched a program P4GN 2011-2015 BNN stage to make 97.2% of the Indonesian population immune to abuse and illicit drug and 2.8% of Indonesia's population (drug abuser) gradually gets medical rehabilitation services and social rehabilitation. BNN of Riau implement programs P4GN to achieve the